Penguatan Agroforestri Berbasis Ketahanan Pangan pada Kelompok Tani Hutan Pujon Hill Malang, Jawa Timur - Nugroho Tri Waskitho; Ramli Ramadhan; Joko Triwanto; Sri Rizki Soleha (LPPM ITB AAS Indonesia Surakarta, 2026)
Agroforestry has been widely practiced by forest farmer groups in forest-edge areas; however, its contribution to household food security and product diversification is often not optimally developed. This community service program aimed to strengthen agroforestry-based food security and livelihood diversification at KTH Pujon Hill, Malang Regency, through the integration of food crops, coffee, and medicinal plants. The program was implemented using a participatory approach involving socialization, training, technology application, and continuous mentoring. Results showed that the integration of medicinal plants into existing agroforestry systems improved land-use efficiency, enhanced farmers’ knowledge and skills, and encouraged simple value addition through herbal beverage processing. Agroforestry practices at KTH Pujon Hill contribute to household food security by ensuring food availability, supporting income generation, and improving microclimatic conditions for crop production. The program highlights the potential of agroforestry-based community empowerment to support sustainable livelihoods and food security in forest-edge communities when supported by continuous assistance and institutional strengthening.